Digitalization: new risks for people with disabilities. Problem statement - N. N. Meshcheryakova; E. N. Rogotneva (Цифровая социология)
The philosophy of independent living implies the possibilities of leading a life independent of third parties for people with disabilities. Digitalization of the most important spheres of activity: education, employment and employment, health care, public administration is considered, among other things, as the most important tool for solving this problem. But, as empirical studies show, the secondary analysis of the results of which is carried out in this article, at the moment, digitalization creates additional social barriers, increasing segregation and exacerbating the inequality of this social community. The availability of modern information and communication technologies and the ability to use them are influenced by both independent factors common for the population (age, education, income, type of settlement), and specific ones inherent only in this social community (nosology and severity of a functional defect). Inattention within the framework of digitalization programs to the fact that disability has an individual trajectory and for the full use of modern information and communication technologies, people with disabilities need assistive technologies, the costs for them, the compatibility of auxiliary software with the design of websites is one of the main reasons for the emergence of digital inequality in this category of the population.To minimize digital barriers, depending on the individual needs of disabled people, it is proposed:1) to expand the functions, competencies and technical capabilities of social workers and / or organize technological support of life activities by volunteers;2) to develop programs of additional information education;3) to calculate the costs of assistive technologies for individual nosologies to provide targeted social assistance;4) to encourage and subsidize the development of assistive technologies within the framework of state financial assistance to high-tech developments;5) to take into account the special needs of people with disabilities in digitalization programs.